Memories in the sun: in search of a dramaturgy of listening with women in deprivation of freedom (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article analyzes an artistic-pedagogical workshop with incarcerated women. The workshop took place in 2019, at the Women’s Prison of Florianópolis, in the State of Santa Catarina, Brazil. Prisons strategically makes its subjects invisible, as their stories are constructed by other people and based on stigmas. The author and her collaborators tried to go against these strategies. Thus, the workshop focused on the development of practices intended to enable the reappropriation and re-signification of the participants’ life stories, using theater. Drawing on the theatrical devising process used with the women, this article attempts not to omit the voices of the women who participated in the workshop but to bring them into focus.
Keywords: Theater Pedagogy; Female prison; Dramaturgy of listening; Memories in the sun